2016
DOI: 10.48550/arxiv.1611.06541
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Koszul duality between Higgs and Coulomb categories $\mathcal{O}$

Abstract: We prove a Koszul duality theorem between the category of weight modules over the quantized Coulomb branch (as defined by Braverman, Finkelberg and Nakajima) attached to a group G and representation V and a category of G-equivariant D-modules on the vector space V . This is proven by relating both categories to an explicit, combinatorially presented category.These categories are related to generalized categories O for symplectic singularities. Letting O Coulomb and O Higgs be these categories for the Coulomb a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…One can apply techniques of the localization theorem in equivariant (K)-homology groups of affine Steinberg varieties in [VV10] to study the category C. This theory, for the ordinary Coulomb branch, will be explained elsewhere [Nak19]. (See also [Web16,Web19] for another approach.) It also works in our current setting.…”
Section: (V)mentioning
confidence: 99%
“…One can apply techniques of the localization theorem in equivariant (K)-homology groups of affine Steinberg varieties in [VV10] to study the category C. This theory, for the ordinary Coulomb branch, will be explained elsewhere [Nak19]. (See also [Web16,Web19] for another approach.) It also works in our current setting.…”
Section: (V)mentioning
confidence: 99%
“…Webster [Web2] proved a general Koszul duality result for category O for Higgs and Coulomb branches (the Koszul duality described in section 6.5 is a special case of this result). This essentially establishes (O).…”
Section: Conical and Hamiltonian Actionsmentioning
confidence: 91%
“…The phase diagrams for the full moduli spaces (including mixed branches) were studied in [31], and it was found that certain theories have Higgs and Coulomb branches which are related by inversion of their phase diagrams. On the other hand, a duality known as symplectic duality between Higgs and Coulomb branches of a 3d N = 4 theory was conjectured in [34] and has been extensively studied in [35][36][37][38][39][40][41][42]. Therefore, for phase diagrams, another question could be raised.…”
Section: The Higgs and Coulomb Branchesmentioning
confidence: 99%